2019
DOI: 10.5539/ijel.v9n3p203
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Anxiety Factors During English Oral Presentation Skills of Engineering Undergraduates in Pakistan

Abstract: This study aims to investigate the factors affecting oral presentation skills of undergraduate-learners of English that influence their academic performance which potentially can affect professional career. The study has used quantitative instrument as questionnaire partially adopted from McCroskey (1982) for data collection among 100 undergraduate-participants on factors affecting oral communication skills at one Public Sector University. Purposive sampling method was used since participants were selected on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Overall, the reviewed studies (Anggita & Suwartono, 2020;Abassi et al, 2019;Soomro et al, 2019;Marx, 2019;Sadiq, 2017;Hwa & Peck, 2017;Tati et al, 2016;Kamaruddin & Abdullah, 2015) that have utilized Horwitz et al's Foreign Language Classroom Anxiety Scale (FLCAS) reported a similar pattern for the causes of presentation anxiety which are mainly due to the fear of negative evaluation from others, lack of language competence, and communication apprehension among students.…”
Section: Gender Differences On Presentation Anxietymentioning
confidence: 93%
See 1 more Smart Citation
“…Overall, the reviewed studies (Anggita & Suwartono, 2020;Abassi et al, 2019;Soomro et al, 2019;Marx, 2019;Sadiq, 2017;Hwa & Peck, 2017;Tati et al, 2016;Kamaruddin & Abdullah, 2015) that have utilized Horwitz et al's Foreign Language Classroom Anxiety Scale (FLCAS) reported a similar pattern for the causes of presentation anxiety which are mainly due to the fear of negative evaluation from others, lack of language competence, and communication apprehension among students.…”
Section: Gender Differences On Presentation Anxietymentioning
confidence: 93%
“…1, June 2022 their presentation anxiety in class. In a similar qualitative study (Soomro et al, 2019) conducted on 100 undergraduate engineering students in Pakistan by investigating the factors that affect their presentation performances through an adopted five-point-likert-scale questionnaire (McCroskey, 1982) regarding oral anxiety. They found out that most of the participants experienced low motivation, nervousness, and low confidence when doing presentations in class.…”
Section: Efl Presentation Anxiety Abroadmentioning
confidence: 99%
“…The findings of these studies have attributed students' CA to a lack of authentic and straightforward sources and a target language that is not their native language and constructs each word differently (Huashan, 2019), inadequate linguistic competencies (Mohamed and Asmawi, 2018), struggle with group communication (Nugroho, 2022) and lack of paralinguistic prerequisites as well as fear that as public speakers, they will attract both attention and criticism (Riaz and Riaz, 2022). CA can occasionally cause brief brain blocks during presentations, causing students to forget or lose sight of ideas (Soomro et al, 2019), which hinders them from speaking fluently in FL settings. As a result, Belaman et al (2022) contended that adopting oral communicative strategies can help students overcome their fear of public speaking.…”
Section: Heswbl 136mentioning
confidence: 99%
“…Some are worried that, as presenters, they are not only the focus of attention but also of criticism [9]. Sometimes nervousness and stage fright lead to temporary mental blocks during the presentation and students forget or lose track of ideas [10].…”
Section: Speech Training Needs Of Students Who Learn English As An Ad...mentioning
confidence: 99%